Erratum to “An enhanced prediction model for the on-line monitoring of the sensors using the Gaussian process regression” (Journal of Mechanical Science and Technology, (2019), 33, 5, (2249-2257), 10.1007/s12206-019-0426-7) - Lee, Sungyeop; Chai, Jangbom (Journal of Mechanical Science and Technology, 2019)
There is one correction to make to the original article. Fig. 4 was published incorrectly. Fig. 4 has to be corrected as follows.